Methods Used to Evaluate Pain Behaviors in Rodents - Deuis, Jennifer R.; Dvorakova, Lucie S.; Vetter, Irina (Frontiers in Molecular Neuroscience, 2017)
Rodents are commonly used to study the pathophysiological mechanisms of pain as studies in humans may be difficult to perform and ethically limited. As pain cannot be directly measured in rodents, many methods that quantify “pain-like” behaviors or nociception have been developed. These behavioral methods can be divided into stimulus-evoked or non-stimulus evoked (spontaneous) nociception, based on whether or not application of an external stimulus is used to elicit a withdrawal response. Stimulus-evoked methods, which include manual and electronic von Frey, Randall-Selitto, and the Hargreaves test, were the first to be developed and continue to be in widespread use. However, concerns over the clinical translatability of stimulus-evoked nociception in recent years has led to the development and increasing implementation of non-stimulus evoked methods, such as grimace scales, burrowing, weight bearing and gait analysis. This review provides an overview, as well as discussion of the advantages and disadvantages, of the most commonly used behavioral methods of stimulus-evoked and non-stimulus-evoked nociception used in rodents.